PERAN KEPALA SEKOLAH DALAM MENANGGULANGI KENAKALAN SISWA SMP SWASTA IRA MEDAN - Abdillah, Putri Anggraini (Hijri, 2020)
This study aims to determine (1) how the role of the principal in dealing with student delinquency at the IRA Medan Private Junior High School, (2) how the supporting factors faced by the principal in overcoming student delinquency in IRA Medan Private Junior High School, (3) and how the inhibiting factors are faced by school principals in overcoming student delinquency at IRA Medan Private Middle School. This research is a qualitative research using descriptive research methods. This research has the character of describing, telling, and producing existing data and producing descriptive data in the form of written / spoken words from people and observable behavior and the data is statement in nature. The technique of collecting data is done through observation, interviews, and documentation. The data analysis technique is descriptive qualitative. Applying data validity, and using data tringulation techniques, namely data validity checking techniques that use as a source outside the data as comparison material..